Investigating the attitudes and perceived drivers of research engagement among academicians of private dental institutes of Lahore, Pakistan - Tariq, Khaloud; Tahir, Sana; Muhammad Hassan; Aslam, Roshaney (Journal of the Pakistan Medical Association, 2026)
Objective: To investigate research attitudes and drivers of research engagement among academicians of private dental institutions in an urban setting. Method: The cross-sectional study was conducted from January to August 2022 after approval from the ethics review board of the University College of Dentistry, University of Lahore, Pakistan, and comprised faculty members of five private dental colleges in Lahore. Data was collected using a self-designed questionnaire that had six items assessing attitudes and seven items evaluating drivers of research engagement. Data was analysed using SPSS 25. Results: Of the 200 subjects approached, 169(84.5%) responded; 107(63.3%) females and 62(36.7%) males. The overall mean age was 30.9±4.79 years. There were 56(33.1%) subjects with postgraduate qualification, and 102(60.4%) had a work experience of 1-5 years. The mean attitude score was 23.19±3.38. Many participants 54(32%) reported having insufficient knowledge to conduct research, and 157(92%) believed that more attention needs to be given to research in teaching institutions. Potential drivers of research engagement were the provision of resources 110(65.1%), appreciation by the institution 150(88.8%), a decrease in academic responsibilities 134(79.3%) and research remuneration 153(90.2%). Participants with undergraduate qualification were significantly different from those with postgraduate education with regard to conducting research if provided with incentives (p=0.04). Conclusions: The attitude of faculty members towards research was found to be moderate. Provision of adequate resources and institutional support may serve as a catalyst for enhancing research engagement. Key Words: Dental research, Academia, Faculty, Dental, Attitude.